If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9m + -9 = 9 Reorder the terms: -9 + -9m = 9 Solving -9 + -9m = 9 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -9m = 9 + 9 Combine like terms: -9 + 9 = 0 0 + -9m = 9 + 9 -9m = 9 + 9 Combine like terms: 9 + 9 = 18 -9m = 18 Divide each side by '-9'. m = -2 Simplifying m = -2
| 13+3p=7 | | 18-7f=4 | | 2q-6=4 | | 5t-4=6 | | x-2*x-5= | | 5w-12=3 | | -10+2d=8 | | 2r-7=-1 | | 2b+4=-8 | | 4x+17=-15 | | 6(x+3)=4 | | 23x-16=14-17x | | 4x+6x+3=-5 | | 7(x-5)=3(x+1) | | 3x+x-9=10 | | 5x+6x-16=3x+2x-4 | | 18x-43=65 | | 2x+1=4x-7 | | y=3x+2 | | 4(2-3p)-2=3(4p-2) | | 4x-8-3x+12=5 | | 7(5x)=6(4) | | 4(2x-3)=-2(3x-8) | | 22-a+5a-3=5-3a | | 7a-8=5a+12 | | 2m+8+3m-3=5 | | 5x-4=11+2x | | 5x-3= | | n-24=9 | | 15=y-7 | | 3=x-16 | | p-8=9 |